Is there a Relationship Between Keros Classification of Olfactory Fossae Depth, Septal Deviation Angle and the Distance Between Infraorbital Foramens? - Inal, Mikail; Muluk, Nuray B.; Arikan, Osman Kursat; Sahin, Safa (Current Medical Imaging, 2018)
Objectives: We retrospectively investigated the relationship between olfactory fossae depth, septal deviation angle, paranasal sinuses and the distance between infraorbital foramens (IOFs). Methods: Computerized Tomography (CT) images of 315 adult subjects were used. Paranasal sinus dimensions; Keros classification of olfactory fossae, length of Crista Galli (CG), the distance between IOFs (ZP), The distance between inferior part of crista galli and basal-inferior part of the nasal septum at the midline (CG-Sbasal) (XY), ZP/XY ratio, septal deviation side and angle were measured. Results: Keros type I was detected in males (50.3%) and Keros type II was detected in females (59.5%) mainly. In females, Keros type was highly related to the males. Both right-deviated and left deviated subjects, Keros type II (49.7% and 54.3% respectively) was the most detected Keros-type for olfactory fossae. Higher ethmoid sinus-height, maxillary sinus-width; and lower maxillary sinusheight values were related to higher Keros types. As IOFs (ZP) distance increased, Keros type also increased. Conclusion: When Endoscopic Sinus Surgery (ESS) is performed in patients having nasal septal deviation, surgeons should be careful for Keros type II olfactory fossae to avoid intracranial penetration. If possible, navigation systems should be used in these patients.
Keywords: septal deviation angle